INTERNSHIP IN INDIAN VOCATIONAL EDUCATION AND STUDENTS’ PERCEPTION: A CASE OF TOURISM AND HOSPITALITY UNDERGRADUATES - Ashutosh, Kumar; Charak, Nikhil; Bhatt, Ketan; Kabia, Sunil Kumar; Gangotia, Amit; Rana, Krishma (Anais Brasileiros de Estudos Turísticos, 2025)
The latest National education policy of India (NEP-2020) underlined the significance of internship opportunities for students pursuing vocational degree programmes to make them job ready for the industry. Internship have always been the most effectual tool for empirical learning, as it allows students to experience hands-on learning as well as the practical aspects of the theory courses. Current research examines the role and importance of internship in tourism and hospitality education. Pondering on the significance of internships in developing skill competencies amongst the students, the findings of current study can be effective in identifying the overall perception of hospitality students in judging their skill competencies during the pre-internship and post-internship period. This research attempts to find out the gap between the pre and post on-the-job training (OJT) experience of tourism and hospitality undergraduates in terms of competencies required to set foot in the industry. The paper is empirical in nature and employs both primary and secondary data which was analysed using mean scores and t-test. The major implication of the study is to assess the significance of the internship in developing industry-relevant competencies among students.